Tourism innovation through relationship marketing and value co-creation: A study on peer-to-peer online platforms for sharing accommodation - Casais, Beatriz Graça Luz (2020)
Supplementary data to this article can be found online athttps://doi.org/10.1016/j.jhtm.2019.11.010